The utility of endoscopic ultrasonography and endoscopy in the endoscopic mucosal resection of early gastric cancer. Issue 4 (1st October 1999) - Ohashi, S; Segawa, K; Okamura, S; Mitake, M; Urano, H; Shimodaira, M; Takeda, T; Kanamori, S; Naito, T; Takeda, K; Itoh, B; Goto, H; et al.
Abstract : OBJECTIVE: To clarify the usefulness of endoscopic ultrasonography (EUS) and endoscopy in the endoscopic mucosal resection (EMR) of early gastric cancer. Patients/Methods —EMR was performed in 61 patients with early gastric cancer over the past five years. The accuracy of the assessment of the depth of cancerous invasion was studied in 49 patients who had EUS before EMR. Forty eight patients were treated with endoscopy alone; in these patients, EUS and endoscopic findings correlated with the clinical course. RESULTS: Forty six patients showed no changes in the submucosal layer or deeper structures on EUS. Pathologically these included 37 patients with mucosal cancer and nine with submucosal cancer showing very slight submucosal infiltration. Three patients showed diffuse low echo changes in the submucosal layer on EUS; pathologically, these included two with submucosal cancer and one with mucosal cancer with a peptic ulcer scar within the tumour focus. Of 48 patients receiving endoscopic treatment alone, 45 showed no tumour recurrence or evidence of metastases on EUS and endoscopy. Three cases of recurrence were observed. Two of these patients had a surgical gastrectomy, and one was re-treated endoscopically. In the former cases, the surgical results correlated well with assessment by EUS and endoscopy. In addition, the latter patient who was re-treated endoscopically after evaluation with EUS and endoscopy has so far had no recurrence. CONCLUSION: The combined use of EUS and endoscopy is effective in diagnosing the depth of cancerous invasion in patients undergoing EMR as well as in clarifying changes both within and between anatomic levels during follow up.